Boosting Zn2+ and NH4+ Storage in Aqueous Media via In‐Situ Electrochemical Induced VS2/VOx Heterostructures. (23rd December 2020) - Yu, Dongxu; Wei, Zhixuan; Zhang, Xinyuan; Zeng, Yi; Wang, Chunzhong; Chen, Gang; Shen, Ze Xiang; Du, Fei
Abstract: Aqueous‐ion batteries have received much attention owing to the merits of high safety, low cost, and environmental friendliness. Among potential cathode candidates, transition metal sulfides drew little attention since they suffer from low capacity, low working potential, and fast capacity fading. Here, advantage is taken of the chemical instability of VS2 in aqueous electrolyte to in situ fabricate a heterostructural VS2 /VO x material. Benefiting from the internal electric field at heterointerfaces, high conductivity of vanadium sulfide and high chemical stability of vanadium oxides, heterostructural VS2 /VO x delivers an enhanced working potential by 0.25 V, superior rate capability with specific capacity of 156 mA h g −1 at 10 A g −1, and long‐term stability over 3000 cycles as Zn 2+ storage electrode. In addition, heterostructural VS2 /VO x is employed as the cathode for aqueous NH4 + ion storage with high reversible capacity over 150 mA h g −1 and long lifespan over 1000 cycles, surpassing the state‐of‐the‐art materials. VS2 /VO x is proved to demonstrate a (de)intercalation process for Zn 2+ storage, while a conversion reaction accompanied by insertion is responsible for nonmetal NH4 + . The strong insight obtained in this study sheds light on a new methodology of exploring the potential of transition metal sulfides‐based cathode materials for aqueous ion batteries. Abstract : The VS2 /VO x heterostrctural material is obtained through an in situ initial charging process. The heterostructure is demonstrated through XRD, FTIR, XPS, and HRTEM. Benefitting from the effect of heterointerface, it exhibits higher capacity, much more stable cycling performance, and better rate capability than that of VS2 in aqueous zinc ion and NH4 + ion batteries.